Analysing the gene expression profiles of the orphan nuclear receptors NR4A1, NR4A2 and NR4A3 in premalignant lesions of the cervix and cervicitis - Rosa P. Cruz-Nieves; Gladys E. Ramírez-Rosales; Javier González-Ramírez; Fausto Sánchez-Muñoz; Armando Ruiz-Hernández (Elsevier, 2024)
Objective: The main objective of the present study was to evaluate the expression of nuclear orphan receptors in the development of Uterine Cervical Cancer (UCC). The principal cause of dysplastic changes in cervical epithelium is the presence of the human papilloma virus leading to the development of cervical intraepithelial neoplasia I (CIN I), high-grade lesions (CIN II and CIN III) and, finally, invasive cancer. Despite the existence of various treatments and vaccines, there is still a high mortality rate. There is evidence of the participation of a group of nuclear receptors called orphans in the development of various diseases, including cancer. Study design: The expression levels of the orphan receptors NR4A1, NR4A2, and NR4A3 were measured using real-time polymerase chain reaction (RT-PCR) in samples obtained through colposcopy from forty-five patients who attended the Medical Oncology Specialties Unit (UNEME) in Mexicali, B.C. Results: Forty-five cervical biopsy results were obtained, indicating cervicitis, CIN I, or CIN III, none of them CIN II. Our results showed that orphan receptors expressed in a specific manner depending on the degree of premalignant lesions. NR4A1 overexpressed in cervicitis (p < 0.05). NR4A3 was significantly expressed in CIN I (p < 0.05) and NR4A2 was expressed in both cervicitis and CIN III (p > 0.05). Conclusion: Our data suggest, for the first time, that nuclear receptors might be involved in the various stages that precede the development of invasive UCC.